Protection of Children’s Personal Data (CPD) in the Digital Environment, Legal Obligations of Online Platforms (OPs) in Indonesia - Nurhabibah, Nurhabibah; Iwari, Dian Puspa; Istiarsyah, Istiarsyah (The Easta Journal Law and Human Rights, 2026)
The rapid expansion of the digital environment has intensified the collection and processing of children’s personal data by online platforms, raising significant legal concerns regarding privacy and child protection. This study examines the protection of Child Personal Data (CPD) in Indonesia by focusing on the legal obligations of Online Platforms (OP) within the digital ecosystem. Employing a normative juridical approach, the research analyzes statutory regulations on personal data protection, electronic systems, and child protection to assess their coherence and effectiveness. The findings indicate that although Indonesia has established a legal foundation recognizing children as a vulnerable group requiring heightened data protection, regulatory fragmentation, limited operational guidance, and enforcement challenges remain. In particular, ambiguities related to consent mechanisms, age verification, accountability standards, and cross-border platform operations weaken the practical protection of children’s data. This study concludes that clearer, more specific, and enforceable legal obligations for online platforms are necessary to ensure effective CPD protection and to strengthen children’s rights in Indonesia’s digital environment.